2007
DOI: 10.1253/circj.71.1067
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum Glycated Albumin Level is Associated With the Presence and Severity of Coronary Artery Disease in Type 2 Diabetic Patients

Abstract: An increased serum level of glycated albumin is associated with the presence and severity of CAD, and may be useful in screening patients with T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 25 publications
2
53
0
4
Order By: Relevance
“…in fact, Pu et al have reported that an increase of ga independent of hba 1c is associated with the presence and severity of coronary artery disease in type 2 diabetic patients [24]. however, the present study has several limitations.…”
Section: Discussionmentioning
confidence: 64%
“…in fact, Pu et al have reported that an increase of ga independent of hba 1c is associated with the presence and severity of coronary artery disease in type 2 diabetic patients [24]. however, the present study has several limitations.…”
Section: Discussionmentioning
confidence: 64%
“…Hyperglycemia is one of the main mechanisms involved in the development of complications in diabetic patients. Previous studies (27)(28)(29) demonstrated the association of high glycated hemoglobin levels with the severity of the CAD and with poorer outcome after percutaneous coronary angioplasty. Recently, Anand et al (30) showed that suboptimal glycemic control is a risk factor for coronary artery calcification progression.…”
Section: Vessel Shrinkage and Atherosclerosismentioning
confidence: 99%
“…Recently, it has been revealed that GA is an index that predicts the development of coronary artery disease (CAD) as well as its severity [30,31]. The relationship between GA and diabetic vascular complications will be further investigated.…”
Section: Postprandial Hyperglycemiamentioning
confidence: 99%